What is the best therapeutic strategy for colonoscopy of colorectal neoplasia? Future perspectives from the East. Issue 3 (9th December 2015) - Shinozaki, Satoshi; Hayashi, Yoshikazu; Lefor, Alan Kawarai; Yamamoto, Hironori
Abstract : Development and improvement of endoscopic techniques and devices have changed the treatment of colorectal tumors over the last decade. For the treatment of diminutive polyps, the cold snare technique of the West is becoming a promising treatment in the East because of its short procedure time and low rate of delayed bleeding by eliminating the delayed effect of electrocautery. Rather than using piecemeal endoscopic mucosal resection or surgical resection for the treatment of large superficial tumors, the technique of the East of endoscopic submucosal dissection (ESD) achieves a high success rate of en bloc R0 resection, enabling detailed pathological evaluation with less invasive treatment. This procedure should also be useful in the West where large colorectal tumors are more frequent than in the East. Regarding outcomes, however, in the literature, the definition of 'curative resection' remains somewhat inconsistent and long‐term outcomes of patients with deep submucosal and/or lymphovascular invasion in the en bloc specimen have not yet been determined. Large prospective, as well as retrospective, studies of these patients are warranted. When colorectal ESD is difficult because of size or location, the pocket‐creation method and/or double‐balloon‐assisted technique may be useful. In the East, high‐quality magnified chromoendoscopy is widely available, and endoscopists try to identify focal submucosal invasion. In the West, a systematic evaluation of surveillance for the prevention of colorectal cancer has been done and is highly refined. The East and West have much to learn from each other.